Method for improving performance of superconducting reinforcing band
By grinding the surface of the metal belt and forming a laminated structure, and then wetting it in the flux, pressurizing the problem of poor interfacial performance of the superconducting reinforcement belt is solved, and its stability and overall quality under the action of electromagnetic force are improved.
Patent Information
- Application Number
- CN202411725609.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-11
AI Technical Summary
The interface performance of existing superconducting reinforcement belts is poor, and it is easy to cause interface damage under the action of electromagnetic force, affecting the normal operation and safety of the equipment.
By grinding the surface of the metal belt to increase the roughness, increasing the bonding force between the metal belt and the solder layer, forming a laminated structure, and then wetting in the flux, pressurizing the gap, filling the flux with flux, and reducing solder layer defects.
It effectively improves the overall quality of the superconducting reinforcement belt, enhances its stability under the action of electromagnetic force, and reduces the possibility of interface failure.
Smart Images

Figure CN119419000A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of superconducting materials, and in particular relates to a method for improving the performance of a superconducting reinforcing tape. Background Art
[0002] Superconducting materials and their applications have always been one of the most active frontier research areas in contemporary science and technology. There are about 30,000 superconducting materials discovered so far, but only Nb2+ is a practical superconducting material. 3 Sn, NbTi, MgB 2 , Bi-based, Y-based and iron-based superconductors, their critical currents are about 18K, 9K, 39K, 110K, 92K and 55K respectively. When the operating temperature is lower than the critical temperature, the superconducting material will be in a superconducting state, which can not only carry current without resistance, but also produce Meissner effect and Josephson effect. It has been widely used in superconducting energy storage, superconducting motors, superconducting cables, superconducting current limiters, superconducting transformers, superconducting magnetic levitation, nuclear magnetic resonance and other fields.
[0003] Among them, Bi-based, Y-based and iron-based superconducting tapes have high critical temperatures and can break free from the constraints of liquid helium and operate in liquid hydrogen and liquid nitrogen environments. They are considered to be the best superconducting materials for nuclear fusion magnets. Bi-based, Y-based and iron-based superconducting tapes are generally brittle and will break under external forces and deformations. Superconducting tapes will produce large bending deformations during the winding of magnets, and will generate large Lorentz forces and thermal stresses during operation. The fracture of the superconducting layer in the superconducting tape may cause the magnet device to quench, affecting the normal operation and safety of the equipment.
[0004] At present, the lamination method is mainly used to weld metal strips with high mechanical properties on both sides of the superconducting tape to prepare superconducting reinforcement tape. This method has a simple preparation process and is suitable for large-scale production. However, after welding, the interface performance of the composite structure is poor and the solder layer has many defects. Under the action of electromagnetic force, the interface is easily damaged. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and provide a method for improving the performance of a superconducting reinforcing tape. The method grinds the surface of a metal tape to increase the roughness of the metal tape and thereby improve the bonding force between the metal tape and the solder layer, places the superconducting tape between two layers of metal tapes to obtain a stacked structure, and then soaks the stacked structure in flux and uses a pressure treatment to fill the gaps in the stacked structure with flux, which can effectively reduce the generation of solder layer defects, and obtains a high-quality superconducting reinforcing tape after cooling, thereby solving the problem that the interface performance of the superconducting reinforcing tape in the prior art is poor and it is easily damaged under the action of electromagnetic force.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for improving the performance of a superconducting reinforcing tape, characterized in that the method comprises the following steps:
[0007] Step 1: polishing the surfaces of the two metal tapes, and then placing the superconducting tape between the two metal tapes to obtain a stacked structure;
[0008] Step 2, placing the stacked structure obtained in step 1 in flux and infiltrating it, and performing a pressurization treatment after the infiltration is completed;
[0009] Step 3: Cooling the laminated structure after the pressurization treatment in step 2 to obtain a superconducting reinforcement tape.
[0010] The above-mentioned method for improving the performance of a superconducting reinforcement tape is characterized in that the superconducting tape in step 1 is one of a YBCO superconducting tape, a Bi-based superconducting tape and an iron-based superconducting tape, and the metal tape contains one or more of the elements gold, silver, copper, iron, cobalt, nickel, aluminum, chromium, zirconium, tantalum, titanium, molybdenum and niobium.
[0011] The above-mentioned method for improving the performance of a superconducting reinforcement tape is characterized in that the roughness Ra of the metal tape after grinding in step 1 is greater than 50 nm.
[0012] The above-mentioned method for improving the performance of a superconducting reinforcement tape is characterized in that the width of the gap between the metal tape and the superconducting tape in step 1 is not greater than 1000 μm, and the width of the metal tape is 0.5 mm to 1 mm greater than the width of the superconducting tape.
[0013] The present invention can control the gap width and utilize the capillary effect to allow the flux to enter the gap; by setting the width of the metal tape to be larger than the superconducting tape, it can prevent the metal tape from being unable to completely cover the superconducting tape, causing the leaked part of the superconducting tape to be damaged during use, thereby affecting the performance of the superconducting reinforcement tape; at the same time, setting the range to 0.5mm to 1mm can prevent the superconducting layer area of the superconducting reinforcement tape from being too small to affect the performance.
[0014] The above-mentioned method for improving the performance of a superconducting reinforcing tape is characterized in that the soaking time in step 2 is not less than 3 seconds.
[0015] The present invention controls the wetting time to complete the filling of the flux in the gap and enables the entire stacked structure surface to be completely adhered by the flux.
[0016] The above-mentioned method for improving the performance of a superconducting reinforcing tape is characterized in that the pressure of the pressurization treatment in step 2 is 10 MPa to 20 MPa.
[0017] The present invention controls the intensity of the pressurization treatment to 10MPa-20MPa, thereby being able to extrude the stacked structure, allowing the flux to fully cover the gaps and form a dense solder layer, while preventing the superconducting core wire inside the superconducting tape from being crushed due to excessive pressure.
[0018] The above-mentioned method for improving the performance of a superconducting reinforcing tape is characterized in that the cooling in step three is performed by spraying liquid nitrogen or liquid-cooled nitrogen.
[0019] The present invention rapidly cools the solder layer by spraying liquid nitrogen or liquid-cooled nitrogen, thereby preventing the flux in the gap of the stacked structure from being affected by external factors before solidification, causing flow and the like, thereby causing defects in the solder layer.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] 1. The present invention increases the roughness of the metal strip by grinding the surface of the metal strip, thereby increasing the contact area between the solder layer and the metal strip, thereby improving the density and the bonding force between the metal strip and the solder layer; by soaking the stacked structure in flux and then applying pressure to fill the gaps in the stacked structure with flux, the defects of the solder layer can be reduced, and a superconducting reinforcement tape is obtained after cooling, thereby improving the overall quality of the superconducting reinforcement tape and preventing it from being easily damaged by electromagnetic force.
[0022] 2. The present invention controls the roughness and width of the metal tape in the stacked structure and the width of the gap between the metal tape and the superconducting tape, so as to allow the flux to smoothly enter the gap of the stacked structure and adhere to the surface of the metal tape and the superconducting tape to form a packaging layer wrapped by the flux and reduce defects.
[0023] 3. The present invention can further reduce the probability of defects in the solder layer by controlling the pressure range of the pressurized treatment and using liquid nitrogen spray or liquid-cooled nitrogen for rapid cooling, effectively improve the tightness of the combination of the metal tape and the superconducting tape in the stacked structure and enhance the interface performance, thereby improving the quality of the superconducting reinforcement tape.
[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a roughness test result diagram of the polished stainless steel belt in Example 1 of the present invention.
[0026] Figure 2 This is a microstructure diagram of the cross section of the superconducting reinforcement tape obtained in Example 1 of the present invention.
[0027] Figure 3 This is a roughness test result diagram of the polished stainless steel belt in Example 2 of the present invention.
[0028] Figure 4 This is a microstructure diagram of the cross section of the superconducting reinforcement tape obtained in Example 2 of the present invention. DETAILED DESCRIPTION
[0029] Example 1
[0030] The method of this embodiment includes the following steps:
[0031] Step 1: polish the surfaces of the two layers of stainless steel belts to a roughness Ra of 325.60 nm, and then place the Bi-2223 superconducting belt between the two layers of stainless steel belts to obtain a stacked structure; the gap width between the stainless steel belt and the Bi-2223 superconducting belt is 100 μm, the width of the stainless steel belt is 4.8 mm, and the width of the superconducting belt is 4.5 mm;
[0032] Step 2: Place the stacked structure obtained in step 1 in the flux and soak it for 5 seconds. After soaking, transfer it to a pressurizing device for a pressurizing treatment at a pressure of 10 MPa.
[0033] Step 3: Cool the laminated structure after the pressurization treatment in step 2 by spraying liquid nitrogen to obtain a superconducting reinforcement tape.
[0034] The stainless steel tape in this embodiment can also be replaced by a nickel alloy metal tape or a copper alloy metal tape, and the Bi-2223 superconducting tape can also be replaced by a YBCO superconducting tape or one of the Bi-based superconducting tapes other than the Bi-2223 superconducting tape.
[0035] The roughness test of the stainless steel strip after grinding in step 1 of this embodiment is carried out, and the results are as follows: Figure 1 As shown, the roughness Ra is measured to be 325.60 nm; the cross section of the superconducting reinforcement tape obtained in this embodiment is subjected to microstructural analysis, as shown in FIG. Figure 2 As shown, the solder layer of the superconducting reinforcement tape has almost no obvious defects, and the stainless steel tape is tightly combined with the superconducting tape. The shear strength of the superconducting reinforcement tape obtained in this embodiment was tested at a temperature of 77K, and the shear strength was measured to be 72.5MPa.
[0036] In summary, the stainless steel tape and the superconducting tape in the superconducting reinforcement tape prepared in this embodiment are tightly combined and have excellent shear resistance, and the solder layer has no obvious defects and good interface performance.
[0037] Example 2
[0038] The method of this embodiment includes the following steps:
[0039] Step 1: polish the surfaces of the two layers of stainless steel belts to a roughness Ra of 133.00 nm, and then place the Bi-2223 superconducting belt between the two layers of stainless steel belts to obtain a stacked structure; the gap width between the stainless steel belt and the Bi-2223 superconducting belt is 100 μm, the width of the stainless steel belt is 4.8 mm, and the width of the superconducting belt is 4.5 mm;
[0040] Step 2: Place the stacked structure obtained in step 1 in the flux and soak it for 5 seconds. After soaking, transfer it to a pressurizing device for a pressurizing treatment at a pressure of 10 MPa.
[0041] Step 3: Cool the laminated structure after the pressurization treatment in step 2 by spraying liquid nitrogen to obtain a superconducting reinforcement tape.
[0042] The roughness test of the stainless steel strip after grinding in step 1 of this embodiment is carried out, and the results are as follows: Figure 3 As shown, the roughness Ra is measured to be 133.00 nm; the cross section of the superconducting reinforcement tape obtained in this embodiment is subjected to microstructural analysis, as shown in FIG. Figure 4 As shown, the solder layer of the superconducting reinforcement tape has almost no obvious defects, and the stainless steel tape is tightly combined with the superconducting tape; the shear strength of the superconducting reinforcement tape obtained in this embodiment was tested at a temperature of 77k, and the shear strength was measured to be 68.2MPa.
[0043] In summary, the stainless steel tape and the superconducting tape in the superconducting reinforcement tape prepared in this embodiment are tightly combined, have excellent shear resistance, and have very few solder layer defects and good interface performance.
[0044] Example 3
[0045] The method of this embodiment includes the following steps:
[0046] Step 1: polish the surfaces of the two layers of stainless steel belts to a roughness Ra of 93.02 nm, and then place the Bi-2223 superconducting belt between the two layers of stainless steel belts to obtain a stacked structure; the gap width between the stainless steel belt and the Bi-2223 superconducting belt is 100 μm, the width of the stainless steel belt is 4.8 mm, and the width of the superconducting belt is 4.5 mm;
[0047] Step 2: Place the stacked structure obtained in step 1 in the flux and soak it for 5 seconds. After soaking, transfer it to a pressurizing device for a pressurizing treatment at a pressure of 10 MPa.
[0048] Step 3: Cool the laminated structure after the pressurization treatment in step 2 by spraying liquid nitrogen to obtain a superconducting reinforcement tape.
[0049] After testing, the roughness Ra of the stainless steel belt after grinding in step 1 of this embodiment is 93.02nm; the solder layer of the superconducting reinforcement belt obtained in this embodiment has almost no obvious defects, the stainless steel belt and the superconducting belt are tightly combined, and the shear strength is 64.4MPa.
[0050] In summary, the stainless steel tape and the superconducting tape in the superconducting reinforcement tape prepared in this embodiment are tightly combined and have excellent shear resistance.
[0051] Example 4
[0052] The method of this embodiment includes the following steps:
[0053] Step 1: polish the surfaces of the two layers of stainless steel belts to a roughness Ra of 293.06 nm, and then place the Bi-2223 superconducting belt between the two layers of stainless steel belts to obtain a stacked structure; the gap width between the stainless steel belt and the Bi-2223 superconducting belt is 90 μm, the width of the stainless steel belt is 5.0 mm, and the width of the superconducting belt is 4.5 mm;
[0054] Step 2: Place the stacked structure obtained in step 1 in the flux and soak it for 5 seconds. After soaking, transfer it to a pressurizing device for a pressurizing treatment at a pressure of 15 MPa.
[0055] Step 3: Cool the laminated structure after the pressurization treatment in step 2 by spraying liquid nitrogen to obtain a superconducting reinforcement tape.
[0056] After testing, the roughness Ra of the stainless steel belt after grinding in step 1 of this embodiment is 293.06nm; the solder layer of the superconducting reinforcement belt obtained in this embodiment has almost no obvious defects, the stainless steel belt and the superconducting belt are tightly combined, and the shear strength is 70.4MPa.
[0057] Example 5
[0058] The method of this embodiment includes the following steps:
[0059] Step 1: polish the surfaces of the two layers of stainless steel belts to a roughness Ra of 202.8 nm, and then place the Bi-2223 superconducting belt between the two layers of stainless steel belts to obtain a stacked structure; the gap width between the stainless steel belt and the Bi-2223 superconducting belt is 150 μm, the width of the stainless steel belt is 5.5 mm, and the width of the superconducting belt is 4.5 mm;
[0060] Step 2: Place the stacked structure obtained in step 1 in the flux and soak it for 7 seconds. After soaking, transfer it to a pressurizing device for a pressurizing treatment at a pressure of 20 MPa.
[0061] Step 3: Cool the laminated structure after the pressurization treatment in step 2 by spraying liquid nitrogen to obtain a superconducting reinforcement tape.
[0062] After testing, the roughness Ra of the stainless steel belt after grinding in step 1 of this embodiment is 202.8nm; the solder layer of the superconducting reinforcement belt obtained in this embodiment has almost no obvious defects, the stainless steel belt and the superconducting belt are tightly combined, and the shear strength is 69.3MPa.
[0063] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for improving the performance of a superconducting reinforcing tape, characterized in that: The method comprises the following steps: Step 1: polishing the surfaces of the two metal tapes, and then placing the superconducting tape between the two metal tapes to obtain a stacked structure; Step 2, placing the stacked structure obtained in step 1 in flux and infiltrating it, and performing a pressurization treatment after the infiltration is completed; Step 3: Cooling the laminated structure after the pressurization treatment in step 2 to obtain a superconducting reinforcement tape.
2. A method for improving the performance of a superconducting reinforcing tape according to claim 1, characterized in that: The superconducting tape in step 1 is one of a YBCO superconducting tape, a Bi-based superconducting tape and an iron-based superconducting tape, and the metal tape contains one or more of the elements gold, silver, copper, iron, cobalt, nickel, aluminum, chromium, zirconium, tantalum, titanium, molybdenum and niobium.
3. A method for improving the performance of a superconducting reinforcing tape according to claim 1, characterized in that: The roughness Ra of the metal belt after grinding in step 1 is greater than 50nm.
4. A method for improving the performance of a superconducting reinforcing tape according to claim 1, characterized in that: In step 1, the width of the gap between the metal tape and the superconducting tape is no greater than 1000 μm, and the width of the metal tape is 0.5 mm to 1 mm greater than the width of the superconducting tape.
5. A method for improving the performance of a superconducting reinforcing tape according to claim 1, characterized in that: The soaking time in step 2 is not less than 3 seconds.
6. A method for improving the performance of a superconducting reinforcing tape according to claim 1, characterized in that: The pressure of the pressurization treatment in step 2 is 10MPa to 20MPa.
7. A method for improving the performance of a superconducting reinforcing tape according to claim 1, characterized in that: The cooling in step 3 is performed by spraying liquid nitrogen or liquid-cooled nitrogen.